Functional analysis of nematode nicotinic receptors - Sleigh, J (Oxford University Press, 2010)
Parasitic nematodes pose a significant threat to the health and economic welfare of communities worldwide, both directly through human disease and indirectly through infection of livestock and crop. At present, anthelmintic drugs such as the nicotinic agonists, which target nematode nicotinic acetylcholine receptors (nAChRs), offer a facile and cost-effective method of controlling both human and animal infection. Unfortunately, the continued heavy reliance on such compounds has led to the inevitable emergence of resistance in many different Nematoda species, thus making the subject of nematode nicotinic receptors of great importance. Using various levamisole-resistant, nAChR subunit mutants of the soil-dwelling nematode Caenorhabditis elegans (viz. unc-29, unc-38 and unc-63) and well-established resistance-monitoring assays, the responses of the different strains to the nicotinic agonists levamisole, morantel, oxantel and pyrantel have begun to be characterized. Wild-type adult C. elegans are relatively unaffected by 1 mM oxantel, contrasting with a developmental retardation of larvae. Also, unc-38 mutants appear to be less refractory to the anthelmintics than the unc-29 and unc-63 animals. In preparation for the use of C. elegans as an ectopic transformation system for parasitic receptor DNA, preliminary biolistic transformation experiments were performed using microparticle bombardment. It was found that transformation of unc-38 animals with myo-3::gfp construct has no significant effect on their ability to thrash in suspension. The mutant characterization data may possibly reflect differential expression of nAChRs at various stages of development. The transformation data suggest that microparticle bombardment has little or no effect on C. elegans, which is essential for future transgenic experiments. In summary, important baseline data on C. elegans nicotinic receptors have been generated and a fundamental transgenic control line in unc-38;myo-3::gfp has been established. This will allow for exciting rescue experiments using parasitic nematode nAChR DNA.